The Role of Islamic Educational Institutions as Rehabilitation Centers: A Case Study of Pesantren - Hadis Purba; Rahayu Fuji Astuti (STAI Hubbulwathan Duri, 2023)
Islamic boarding schools are a typical wealth of Indonesian Islamic cultural treasures that have at least three elements, namely kiai, santri, and mosque. This research uses a qualitative descriptive approach with a case study method, where researchers try to understand the express and implied meaning behind the phenomena obtained through in-depth interviews, observations, supporting documents, and the results of theoretical studies from various authoritative written sources. This data analysis is carried out circularly by starting with data collection, data presentation, data reduction to conclusions. The results of this study showed that the condition of drug addicts and mental issues at Al-Qodir Islamic Boarding School experienced acute dependence and generally had weak religious knowledge. Islamic religious education materials applied at Al-Qodir Islamic Boarding School are faith education, moral education, and worship education using various varied methods and relevant repression techniques so that students who are addicted to drugs and mental issues can understand and live Islamic religious education comprehensively. The conclusion of this study shows that Islamic religious education has a very important role in the rehabilitation process gradually, systematically and planned by integrating medical, psychological, social and spiritual sciences for the realization of positive changes displayed by drug addicts and mental issues through the level of faith, forging akhlakul karimah, and habituation of worship. The research has implications for the importance of Kyai's role as a leader in managing the dynamics of internal and external changes in pesantren.